2022
DOI: 10.3390/w14121920
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Climate Change on Soil Water Content in Southern Saskatchewan, Canada

Abstract: The main objective of this research was to understand the effects of climate change on soil water content (SWC) across the Qu’Appelle River basin in southern Saskatchewan, Canada. The Soil and Water Assessment Tool (SWAT) and output from 11 high-resolution (0.22°) regional climate models (RCM) were used over three 30-year periods: the near future (2021–2050) and distant future (2051–2080) and the historical reference (1975–2005). The RCM data are from the CORDEX North American domain, which employs the RCP8.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Especially, incorporating a climate model by considering its performance in precipitation and temperature simulations is very important to pave the way for further study and understanding of climate change's impacts on surface runoff, sediment yield, and groundwater [15,16]. e development of a new RCM leads to another opportunity for scientists to analyze the effects of climate change in a discrete manner that relies on a regional rather than global context [17,18]. But climate models that have been developed with the specified resolution are not consistently predicting and simulating the climate variables that are intended to cause climate change [19].…”
Section: Introductionmentioning
confidence: 99%
“…Especially, incorporating a climate model by considering its performance in precipitation and temperature simulations is very important to pave the way for further study and understanding of climate change's impacts on surface runoff, sediment yield, and groundwater [15,16]. e development of a new RCM leads to another opportunity for scientists to analyze the effects of climate change in a discrete manner that relies on a regional rather than global context [17,18]. But climate models that have been developed with the specified resolution are not consistently predicting and simulating the climate variables that are intended to cause climate change [19].…”
Section: Introductionmentioning
confidence: 99%
“…By outlining the level of contribution of human activities and climate change to runoff, it is shown that the level of contribution of human activities to the reduction of runoff is greater than the contribution of climate change [5]. Increased temperature extremes and decreased soil water content (SWC) can result in severe yield reductions with negative impacts on growth stages for local crops such as wheat and canola [6].…”
Section: Introductionmentioning
confidence: 99%